Quantitative Assessment of Parental Somatic Mosaicism for Copy‐Number Variant (CNV) Deletions. (16th March 2020) - Liu, Qian; Grochowski, Christopher M.; Bi, Weimin; Lupski, James R.; Stankiewicz, Paweł
Abstract: As genome sequencing methodologies have become more sensitive in detecting low‐frequency rare‐variant events, the link between post‐zygotic mutagenesis and somatic mosaicism in the etiology of several human genetic conditions other than cancers has become more clear. Given that current clinical‐genomics diagnostic methods have limited detection sensitivity for mosaic events, a copy‐number variant (CNV) deletion inherited from a parent with low‐level (<10%) mosaicism can be erroneously interpreted in the proband to represent a de novo germline event. Here, we describe three sensitive, precise, and cost‐efficient methods that can quantitatively assess the potential degree of parental somatic mosaicism levels for CNV deletions: droplet digital PCR (ddPCR), PCR amplicon–based next‐generation sequencing (NGS), and quantitative PCR. ddPCR using the EvaGreen fluorescent dye protocol can specifically quantify the deleted or non‐deleted alleles by analyzing the number of droplets positive for a fluorescent signal for each event. PCR amplicon–based NGS assesses the allele frequencies of a heterozygous single‐nucleotide polymorphism within a deletion region. The difference in number of reads between the two genotypes indicates the level of somatic mosaicism for the CNV deletion. Quantitative PCR can be applied where the relative quantity of the deletion junction–specific product represents the level of mosaicism. Clinical implementation of these quantitative variant‐detection methods enables potentially more accurate assessment of disease recurrence risk in family‐based genetic counseling, allowing couples to engage in more informed family planning. © 2020 by John Wiley & Sons, Inc. Basic Protocol : Droplet digital PCR (ddPCR) Alternate Protocol 1 : PCR amplicon–based next‐generation sequencing Alternate Protocol 2 : Quantitative real‐time PCR (qPCR)